Resilience beyond expectations: seedling performance under fire and grazing pressure in old-growth Andean Araucaria araucana forests - Bernardita Diaz-Mons; Bernardita Diaz-Mons; Bernardita Diaz-Mons; Paola Arroyo-Vargas; Paola Arroyo-Vargas; Rodrigo Vargas-Gaete; Rodrigo Vargas-Gaete; Rodrigo Vargas-Gaete; Leonardo Almonacid-Muñoz; Leonardo Almonacid-Muñoz; Héctor Herrera; Héctor Herrera; et al. (Frontiers in Forests and Global Change)
Altered fire regimes are mainly driven by anthropogenic factors and amplified by climate anomalies globally. Biological legacies that persist after fire are key for the post-fire vegetation recovery, facilitating the establishment and growth of new plant cohorts. However, these effects on long-lived conifers from southern South America still remains unclear. In this study, we experimentally evaluated the effect of biological legacies and cattle activity on seedling survival and growth of the conifer Araucaria araucana (monkey puzzle tree) in fire-affected forests in south-central Chile. Biological legacies in the burned areas included fallen logs, standing dead trees and understory canopy cover, which are hypothesized to have positive effects on seedling performance when facing harsh post-fire site conditions. These effects would be more beneficial within areas subjected to cattle activity after severe fires. Araucaria araucana seedlings were planted within burned forests affected with moderate and high fire severity, comparing both the presence and absence of post-fire biological legacies and cattle activity, and monitored for 5 years. Results revealed that the overall seedling survival rate was generally good, ranging from 79–83% in moderate and high fire severity, respectively. The effect of biological legacies on seedling survival was in general positive, but not significant across all conditions. We found a significant positive effect on plant height growth when biological legacies were nearby and when cattle were excluded, particularly in burned forests with high fire severity. Neither post-fire biological legacies nor cattle exclusion showed a positive effect on the number of new shoots or plant collar growth. In summary, A. araucana is well capable of surviving and growing in absence of biological legacies or when preventing cattle into burned areas, highlighting its great resilience capacity to recover after severe forest fires. Yet, these practices may benefit post-fire vegetation recovery in the long-term and could be considered when feasible.